Analysis of Road Damage and Its Improvement on The South Ring Road of Jambi City - Laksana, Tendy Laksana; Agustien, Melawaty; Kadarsa, Edi (Universitas Sulawesi Barat, 2025)
Analysis of Road Damage and Improvement on the South Ring Road and West Ring Road of Jambi City. Road damage is an event that causes a road pavement to become inconsistent with its original shape. This study, in addition to assessing road conditions in Jambi Province, primarily analyzes the differences between the PCI Method, the Bina Marga Method, and the Asphalt Institute Method. The three methods will be compared by how they are used to determine the condition of the road pavement for the same road section. Then, the calculation process and results will be analyzed to determine which method is easier in conducting surveys and calculations, while other methods are relatively more difficult when applied to the research location. Based on the analysis results on the South Ring Road and West Ring Road sections of Jambi City using the Bina Marga Method, the PCI (Pavement Condition Index) Method, and the Asphalt Institute Method have relatively similar assessments in terms of handling. For handling road damage on the South Ring Road and West Ring Road sections of Jambi City, the PCI (Pavement Condition Index) Method and the Asphalt Institute Method are used in their handling. Kerusakan jalan merupakan kejadian yang mengakibatkan suatu perkerasan jalan menjadi tidak sesuai dengan bentuk perkerasan aslinya. Penelitian ini selain menilai kondisi jalan di Provinsi Jambi, utamanya adalah untuk menganalisis perbedaan dari Metode PCI, Metode Bina Marga, Metode Asphalt Institute. Ketiga metode akan dibandingkan dengan cara dipergunakan untuk menentukan kondisi perkerasan jalan untuk ruas jalan yang sama. Kemudian akan dianalisis proses perhitungan dan hasil sehingga metode apa yang lebih mudah dalam pelaksanaan survei dan perhitungan, sementara metode lain relatif lebih sulit jika diterapkan pada lokasi penelitian. Berdasarkan hasil analisis pada ruas Jalan Lingkar Selatan dan Jalan Lingkar Barat Kota Jambi menggunakan Metode Bina Marga, Metode PCI (Pavement Condition Index), Metode Asphalt Institute memiliki penilaian yang relatif hampir sama dalam penanganan. Untuk penanganan kerusakan jalan pada ruas Jalan Lingkar Selatan dan Jalan Lingkar Barat Kota Jambi menggunakan Metode PCI (Pavement Condition Index) dan Metode Asphalt Institute dalam penanganannya.